FOKUS BELAJAR SISWA DALAM MENGIKUTI MATA PELAJARAN IPAS - Yara Biduri; Rohani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article discusses students’ focus on learning in the IPAS subject at elementary schools within the context of the Merdeka Curriculum. The integration of Science (IPA) and Social Studies (IPS) into IPAS aims to provide a holistic and contextual learning experience, but it presents challenges in maintaining students’ concentration. Factors influencing focus include cognitive, affective, and psychomotor aspects. Data analysis and studies indicate that students’ levels of attention vary and are affected by teaching methods, the environment, and their understanding of concepts. Innovative teaching strategies and a conducive learning environment are required to sustain students’ focus, making the learning process more effective. This research highlights the importance of managing students’ focus to achieve optimal educational goals at the elementary level.